Virtual Restoration of the Roman wall of León: a diachronic view - Ángel Morillo; Oihan Mendo; Diego Prieto; Gema Duprado; Silvia Bonacasa (Virtual Archaeology Review)
The Roman wall, of rectangular plan and rounded corners, following the canonical military model, is the major evidence of the fortress built by the Legion VII Gemina in León in 74 AD. The archaeological interventions developed throughout the decades have confirmed that the defensive system consists of two adjacent walls: the first one dates back to the Low Empire, while the other, attached to the previous one by its external face, is dated Late Third to Early Fourth century AD. We, too, must add an internal rampart (agger) corresponding to a previous defensive system. The 3D virtual restitution we have undertaken allows us to contemplate, with further detail, the features of this almost 20 meters wide constructive complex that has conditioned the urban development of the city of León.